Needle and syringe programs in Yunnan, China yield health and financial return - Xun Zhuang; Wu Zunyou; Yap Lorraine; Zhang Lei; Wilson David P (BMC, 2011)
Abstract Background As a harm reduction strategy in response to HIV epidemics needle and syringes programs (NSPs) were initiated throughout China in 2002. The effectiveness of NSPs in reducing the spread of infection in such an established epidemic is unknown. In this study we use data from Yunnan province, the province most affected by HIV in China, to (1) estimate the population benefits in terms of infections prevented due to the programs; (2) calculate the cost-effectiveness of NSPs. Methods We developed a mathematical transmission model, informed by detailed behavioral and program data, which accurately reflected the unique HIV epidemiology among Yunnan injecting drug users (IDUs) in the presence of NSPs. We then used the model to estimate the likely epidemiological and clinical outcomes without NSPs and conducted a health economics analysis to determine the cost-effectiveness of the program. Results It is estimated that NSPs in Yunnan have averted approximately 16-20% (5,200-7,500 infections) of the expected HIV cases since 2002 and led to gains of 1,300-1,900 DALYs. The total $1.04 million spending on NSPs from 2002 to 2008 has resulted in an estimated cost-saving over this period of $1.38-$1.97 million due to the prevention of HIV and the associated costs of care and management. Conclusion NSPs are not only cost-effective but cost-saving in Yunnan. Significant scale-up of NSPs interventions across China and removal of the societal and political barriers that compromise the effects of NSPs should be a health priority of the Chinese government.